Modulation of Chlamydomonas reinhardtii flagellar motility by redox poise - Wakabayashi, Ken-ichi (The Rockefeller University Press, 2006)
Redox-based regulatory systems are essential for many cellular activities. Chlamydomonas reinhardtii exhibits alterations in motile behavior in response to different light conditions (photokinesis). We hypothesized that photokinesis is signaled by variations in cytoplasmic redox poise resulting from changes in chloroplast activity. We found that this effect requires photosystem I, which generates reduced NADPH. We also observed that photokinetic changes in beat frequency and duration of the photophobic response could be obtained by altering oxidative/reductive stress. Analysis of reactivated cell models revealed that this redox poise effect is mediated through the outer dynein arms (ODAs). Although the global redox state of the thioredoxin-related ODA light chains LC3 and LC5 and the redox-sensitive Ca(2+)-binding subunit of the docking complex DC3 did not change upon light/dark transitions, we did observe significant alterations in their interactions with other flagellar components via mixed disulfides. These data indicate that redox poise directly affects ODAs and suggest that it may act in the control of flagellar motility.